Discussion of Metro Vehicle Traction Control under Washing Mode - YU Tailiang; ZHANG Ming (机车电传动)
Metro vehicle had low target speed under washing mode, which put forward higher requirements on traction system. Taking Wuxi metro line 1 as example, metro vehicle traction control under washing mode was discussed in detail. With speed-torque closed-loop control, brake releasing threshold was regulated to keep vehicle speed stable, which improved washing-mode speed control under the third rail supplying.